2014
DOI: 10.1016/j.ajo.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Wide-Field Fluorescein Angiography and 9-Field Montage Angiography in Uveitis

Abstract: Purpose To qualitatively and quantitatively compare Optos© fundus camera fluorescein angiographic images of retinal vascular leakage with 9-field montage Topcon© fluorescein angiography (FA) images in patients with uveitis. We hypothesized that Optos images reveal more leakage in uveitis patients. Design Retrospective, observational case series. Methods Images of all uveitis patients imaged with same-sitting Optos FA and 9-field montage FA during a 9 month period at a single institution (52 eyes of 31 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…This would typically lead to overestimation of the size of a peripheral lesion, since ophthalmologists often refer to reference structures in the posterior pole to estimate size of other objects in the fundus. For example, previous studies have described conversion rates for areas measured in pixels by assessing the number of pixels in central landmarks such as the optic disc21 or the retinal vein diameter at the margin of the disc,14 and deriving a conversion rate for pixels 2 to mm 2 . These methods, however, do not account for peripheral warp of UWF images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This would typically lead to overestimation of the size of a peripheral lesion, since ophthalmologists often refer to reference structures in the posterior pole to estimate size of other objects in the fundus. For example, previous studies have described conversion rates for areas measured in pixels by assessing the number of pixels in central landmarks such as the optic disc21 or the retinal vein diameter at the margin of the disc,14 and deriving a conversion rate for pixels 2 to mm 2 . These methods, however, do not account for peripheral warp of UWF images.…”
Section: Discussionmentioning
confidence: 99%
“…UWF imaging technology has been applied to colour fundus photography,3 fluorescein angiography (FA),4–6 fundus autofluorescence,7 8 and, more recently, indocyanine green angiography 9. UWF imaging has been shown to be of relevance in many common retinal diseases, including diabetic retinopathy,5 10–12 age-related macular degeneration,7 retinal vein occlusion (RVO),6 13 uveitis14 and retinal dystrophies 15 16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to DR, UWF imaging enabled clear visualization of the areas of neovascularization and peripheral nonperfusion, which requires sector photocoagulation, hence minimizing complications. Compared to 9-field standard FA, UWF FA found significantly more leakage even in areas captured well with standard angiography such as the posterior pole in uveitis [51]. In addition, UWF FAF is useful in determining whether lesions are in a state of active inflammation in patients with uveitis.…”
Section: Uveitis and Retinal Vasculitismentioning
confidence: 98%
“…[4][5][6] A review of data from more than 3 years of research with UWF imaging confirmed that that 66% of clinically relevant retinal pathology is found outside the reach of conventional fundus photography. 7 In our perioperative assessments, the functional capabilities of Optos systems make UWF imaging a useful adjunct to OCT and other standard examination tools, particularly in providing an efficient way to examine the retinal periphery.…”
mentioning
confidence: 99%